Formation of the popliteal muscle in human ontogenesis - Hajnowska-Cieślik, Krystyna (Anthropological Review, 1978)
The aim of this paper is to supply anthropometric data on popliteal muscle of human fetuses (the material comprising 100 extremities) and to describe its developmental changes during intrauterine life. In order to show direction and extent of changes fetal muscles were compared with those of adults (measured on 34 extremities) and monkeys (10 lower limbs of Cercopithecus sabaeus). It has been found that analysed metric characters of the muscle have similar directions of development and variability; during the investigated period of fetal ontogeny variability increases with age. Analysis of metric characters and quotient indices has shown that with age elongation of tendon relative to fleshy part of the muscle occurs. Analysis has also revealed differences between fetuses and adults with respect to development and form of the muscle. There are similarities between popliteal muscles of mokeys and human adults while muscles of fetuses are considerably different from those in the set of compared characteristics.